American surveillance : intelligence, privacy, and the Fourth Amendment - Gregory, Anthony, 1981- (The University of Wisconsin Press, 2016)
Some see domestic intelligence gathering as a crucial task of national security, regardless of personal privacy. Others warn against a surveillance state that tramples constitutional rights. The idea of a total information state has both inspired and frightened Americans. In confronting these controversies, people appeal to law, liberty, or foreign policy to argue for or against surveilling the citizenry. The polarizing topics of surveillance, intelligence, privacy, and Fourth Amendment protections often produce more heat than light. Anthony Gregory offers a nuanced history and analysis of these vexing questions. He highlights the complex relationships between foreign and domestic intelligence, and between national security surveillance and countervailing efforts to safeguard individual privacy. The Fourth Amendment prohibiting unreasonable searches and seizures offers no panacea, he finds, in combating assaults on privacy--whether by the NSA, the FBI, local police, or more mundane administrative agencies. And, he notes, some of the high-stakes issues provoked by intelligence methods have little to do with privacy. Given the advancement of technology, together with the ambiguities and practical problems of Fourth Amendment enforcement, Gregory emphasizes that privacy advocates need to consider multiple policy fronts. -- Provided by publisher.